Feeling Under Pressure: Perspectives of the Meaning of Love and Sexual Relationships Amongst Young Men in KwaZulu-Natal Province, South Africa. Issue 2 (March 2019) - Manyaapelo, Thabang; Sifunda, Sibusiso; Ruiter, Robert A.C.; Nyembezi, Anam; van den Borne, Bart; Reddy, Priscilla
This study aimed to explore perspectives on the meaning of love and sexual relations amongst young men in KwaZulu-Natal province of South Africa. Gaining insights into these perspectives will help to understand the sexual behaviors of these young men better and to eventually develop more effective HIV prevention interventions. Focus group discussions were conducted in two study areas using a predetermined semistructured discussion guide. The findings indicate that the phenomenon of romantic relationship try-outs together with the idea of "feeling under pressure" to propose love to more than one woman seem to be accepted practices that often lead to multiple concurrent sexual partners and therefore potentially risky sexual behaviors. The fear of impregnating a woman is seen to be of a more significant concern than acquiring a sexually transmitted infection due to the stigma and embarrassment associated with pregnancy outside marriage. Given these findings, it is recommended that future studies investigate perspectives on sexuality and reproductive health in male populations in great detail prior to the development of behavioral change interventions because failure to do so may hamper well-intended but poorly targeted health interventions.